1966
DOI: 10.1080/00288233.1966.10420780
|View full text |Cite
|
Sign up to set email alerts
|

Palatability characteristics of crossbred lambs as related to individual southdown sires, slaughter age, and carcass fatness

Abstract: The influence of sire and age on the palatability characteristics of rib-loins from Southdown X Romney lambs was studied. Twelve lambs were selected from each of six Southdown sire groups, and one-third of these lambs were slaughtered at 17, 22, and 27 weeks of age respectively. Neither taste panel nor tenderometer detected any over-all effect due to sire on tenderness, and panel scores for texture, juiciness, and flavour of cooked meat did not vary significantly between sires. Both the taste panel scores and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

1969
1969
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 3 publications
0
7
1
1
Order By: Relevance
“…Nevertheless, fat eects on palatability traits remain controversial in lamb (Jeremiah, 1998) and some authors did not ®nd tenderness dierences in carcasses with signi®cant dierences in fatness (Crouse et al, 1982;Drans®eld et al 1990;Jeremiah et al, 1972;Woodhams et al, 1965). Juiciness dierences were not signi®cant, contrary to the general opinion that this taste trait increases with fatness (Jeremiah, 1996;Kemp et al 1972;Woodhams et al, 1965). This could be explained by the juiciness interpretation made by our panel.…”
Section: Sensory Meat Qualitycontrasting
confidence: 53%
See 1 more Smart Citation
“…Nevertheless, fat eects on palatability traits remain controversial in lamb (Jeremiah, 1998) and some authors did not ®nd tenderness dierences in carcasses with signi®cant dierences in fatness (Crouse et al, 1982;Drans®eld et al 1990;Jeremiah et al, 1972;Woodhams et al, 1965). Juiciness dierences were not signi®cant, contrary to the general opinion that this taste trait increases with fatness (Jeremiah, 1996;Kemp et al 1972;Woodhams et al, 1965). This could be explained by the juiciness interpretation made by our panel.…”
Section: Sensory Meat Qualitycontrasting
confidence: 53%
“…Greater amounts of fat (or high energy diets) are associated with lower shear force values in ruminant meat (Jeremiah et al, 1972;Smith et al, 1976;Babiker et al, 1990;Devine, Grafhuis, Muir & Chrystall, 1993). However, some studies in fatter animals have shown that marbling is not closely related to instrumental measurements of tenderness (Woodhams, Kirton & Jury, 1965), especially in animals with similar growth rates (Dubeski et al, 1997). Light carcasses with generally low subcutaneous fat thickness would have much less marbling than in many other published studies.…”
Section: Instrumental Meat Qualitymentioning
confidence: 59%
“…Absence of sire effects on tenderness as found in Experiments 2, 4, 5, and 6 is, however, not uncommon (King and Bland 1960;Broadbent and Bowman 1964;Fox, Eller, Sather, and McArthur 1964;Woodhams et al 1966) and appears to be due mainly to the large variation between individuals within sire groups. Ray and Mandigo (1966) found that tenderness of lambs differed according to the breeding of the dams.…”
Section: Sire Effectsmentioning
confidence: 97%
“…Bell, and Hamalainen (1944) ;Batcher, Dawson, Pointer, and Gilpin (1962) ;Carpenter, King, Orts, and Cunningham (1964); Carpenter and King (1965);Woodhams et al (1966) have each concluded that the effect of fat content on tenderness in lamb is negligible or nonexistent. However, Riley and Field (1967) in their study involving 299 white-faced lambs found that marbling was significantly correlated with Warner-Bratzler shear values.…”
Section: Miscellaneous Effectsmentioning
confidence: 99%
See 1 more Smart Citation